Analisis Pengendalian Kualitas dengan Menggunakan Metode Statistical Quality Control untuk Meminimumkan Produk Cacat - Zalva Arkani; Muhardi; Umari Abdurrahim Abi Anwar (Bandung Conference Series: Business and Management, 2023)
Abstract. PT TOP-F Cikarang is a company engaged in the field of fiteration specialists. The purpose of this study is to determine the quality control carried out by PT TOP-F and the tendency of defects, causes, viewing defects and the impact of these defects with the analysis of Statistical Quality Control methods and 7 tools namely check sheets, histograms, scatter charts, pareto charts, control charts P char, and fishbone charts. The results of the study There are 2 types of defects in Mesh Pack products with different percentages of defects, namely wire broken 61%, and distressed end pressn machine 39%. Where these defects are caused by man factors that are less careful during the process of making these products, settings that are less or incorrect. There are 2 types of defects in Round Filter products with different percentages of defects, namely Scratch 60% and Nickell Peel Off 40%. Where the defect is caused by several factors, namely man who is less careful during the manufacturing process of the product, improper settings and also defects in the material or raw material. Actions that must be improved or carried out by the company are to make data collection regarding defective products, so that it can be a reference or calculation in order to reduce or no defective products are produced again. Checking the material in the warehouse before use in order to reduce the defects produced. Abstrak. PT. TOP- F Cikarang merupakan perusahaan yang bergerak di bidang spesialis fiterasi. Tujuan dari penelitian ini untuk mengetahui pengendalian kualitas yang dilakukan oleh PT. TOP- F dan kecenderungan cacat, penyebab, melihat kecacatan dan dampak dari kecacatan tersebut dengan analisis metode Statistical Quality Control dan 7 tools yaitu check sheet, histogram, scatter chart, pareto chart, control chart P char, dan fishbone chart. Hasil penelitian Terdapat 2 jenis cacat pada produk Mesh Pack dengan presentase kecacatan yang berbeda, yaitu wire broken 61%, dan tertekan mesin pressn end 39%. Dimana kecacatan tersebut disebabkan oleh faktor man yang kurang teliti saat proses pembuatan produk tersebut, settingan yang kurang atau tidak tepat. Terdapat 2 jenis cacat pada produk Round Filter dengan presentase kecacatan yang berbeda, yaitu Scratch 60% dan Nickell Peel Off 40%. Dimana kecacatan tersebut disebabkan oleh beberapa faktor yaitu man yang kurang teliti pada saat proses pembuatan produk tersebut, settingan yang kurang tepat dan juga kecacatan pada material atau raw material. Tindakan yang harus ditingkatakn atau dilakukan oleh perusahaan yaitu membuat pendataan mengenai produk yang cacat, agar dapat menjadi acuan atau perhitungan agar mengurangnya atau tidak adanya produk cacat yang dihasilkan lagi. Mengecek material di gudang sebelum digunakan agar mengurangi kecacatan yang dihasilkan.